Semiconducting Polymer Nanoparticles with Intramolecular Motion‐Induced Photothermy for Tumor Phototheranostics and Tooth Root Canal Therapy. Issue 17 (25th March 2022) - Duan, Xingchen; Zhang, Qianyu; Jiang, Yu; Wu, Xinying; Yue, Xin; Geng, Yanhou; Shen, Jing; Ding, Dan
Abstract: Much effort is devoted to develop agents with superior photoacoustic/photothermal properties for improved disease diagnosis and treatment. Herein, a new fused two isoindigo (DIID)‐based semiconducting conjugated polymer (named PBDT‐DIID) is rationally designed and synthesized with a strong near‐infrared absorption band ranging from 700 to 1000 nm. Water‐dispersing nanoparticles (NPs) of PBDT‐DIID are prepared with good biocompatibility and a rather high photothermal conversion efficiency (70.6%), as the active excited‐state intramolecular twist around the central double bonds in DIID permits most of the absorbed excitation energy flow to heat deactivation pathway through internal conversion. The photoacoustic signal can be further magnified by incorporation of polylactide (PLA) in the NP core to confine the generated heat of PBDT‐DIID within NPs. The resultant doped NPs show excellent performance in photoacoustic imaging‐guided photothermal therapy in an orthotopic 4T1 breast tumor‐bearing mouse model. It is also found that the photothermal effect of the PBDT‐DIID NPs is safe and quite efficacious to highly improve the root canal treatment outcome by heating the 1% NaClO solution inside the root canal upon 808 nm laser irradiation in a human extracted tooth root canal infection model. Abstract : Fused two isoindigo (DIID)‐based semiconducting polymer nanoparticles are designed and synthesized with high near‐infrared light‐harvesting capacity, excellent photothermal conversion property due to the active excited‐state intramolecular twist around the central double bonds in DIID, and amplified photoacoustic signal by enlarging the Grüneisen parameter. The nanoparticles give effective performances in photoacoustic imaging‐guided photothermal therapy of tumors and tooth root canal therapy.